Desdobramentos da impressão na arte contemporânea - Edna Mara de Moura Nunes (2003)
This thesis contains an investigation into printing and the impact of thismedium on contemporary art. To write it, I based myself on my own experience both as an artist and an educator. Considering my artistic work still in a stage of development, I relinquished confronting it directly and opted instead for making the object of my study the printing process as used in a corpus of investigation work by artists whose printing processes run parallel to mine. This corpus comprised a workpiece by each of the following artists: Jean Dubuffet, Robert Rauschenberg, Luciano Fabro and Giuseppe Penone. I looked into the printing process used in the production of each of the said work pieces, trying to detect possible similarities between them while focusing mainly on their particularities. The said art pieces guided me in my effort to build a theoretical thought, working as interlocutors in a dialogue with a pre-established theoretical field comprised of texts written by Didi-Huberman for the catalogue of LEmpreinte and Walter Benjamins text titled The work of art in the time of mechanical reproduction. These texts allowed me to reflect on the expansion of the printing concept, on its anachronistic character and also on the issue of the technical reproducibility of an image. Based on an expanded concept of printing, I correlated the above art pieces to other media, such as drawing,engraving, sculpture and painting, considering them from their opening power or within an expanded field as done by Rosalind Krauss with respect to American sculpture in the 1970s.